Facing Economic Uncertainty: Adaptive Audit Strategies - Rumasukun, Mohammad Ridwan (Manunggal Halim Jaya, 2024)
: This qualitative study delves into adaptive audit strategies amid economic uncertainty to investigate auditors' navigation of uncertain economic landscapes. Through a systematic review of relevant literature, employing purposive sampling and thematic analysis, the research aims to uncover key insights. Findings reveal that auditors deploy various adaptive practices, including integrating data analytics and advanced technologies, adopting risk-based auditing approaches, and utilizing scenario planning techniques. These strategies enhance audit quality, efficiency, and effectiveness by identifying patterns, prioritizing audit procedures, and assessing financial resilience. Challenges such as data privacy concerns and the need for technical expertise are identified. Future research opportunities include exploring the impact of emerging technologies on audit practices and assessing auditors' role in environmental, social, and governance factors. Overall, the study underscores the importance of agility, innovation, and adaptability in contemporary audit practices, offering valuable insights for auditors and organizations confronting economic uncertainty.